Responsible Tourism Concepts, Theory and Practice - Leslie, David (CABI, 2014)
This text is not about ‘responsible tourism’ in the sense that it might be considered as just another form of tourism such as ‘sustainable tourism’, ‘soft tourism’ or ‘ecotourism’. Neither is it a collage of articles each of which is based on some diff erent type or form of tourism product. Rather, the primary intent is to produce a broad, yet comprehensive, mono- graph on the concept of responsible tourism (RT), focusing on what is meant by the term and what it encompasses. The text thus presents a critical discourse on what RT is, its key tenets and the extent to which they are applied and realized through illustrations and examples of responsibility (or otherwise) in tourism in practice. In pursuance of this objective, the ﬁ rst consideration is to establish a broad context within which to place the emergence of RT and thereby establish a framework to delineate our discourse and establish both structure and content for the following chapters. The use of the term ‘responsible’ in this context implies ‘responsible for’, implying that those involved in tourism are responsible for the consequences of tourism as an activity. For example, responsible providers of tourism products and services may be considered liable for the conduct and outcomes of their operations and trustworthy in their intent. To a greater or lesser extent, this expectation of responsible behaviour is equally applicable to any business activity.